2018
DOI: 10.1002/jcp.27683
|View full text |Cite
|
Sign up to set email alerts
|

The role of nervous system in adaptive response of bone to mechanical loading

Abstract: Bone tissue is remodeled through the catabolic function of the osteoclasts and the anabolic function of the osteoblasts. The process of bone homeostasis and metabolism has been identified to be co‐ordinated with several local and systemic factors, of which mechanical stimulation acts as an important regulator. Very recent studies have shown a mutual effect between bone and other organs, which means bone influences the activity of other organs and is also influenced by other organs and systems of the body, espe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 119 publications
(157 reference statements)
0
16
0
1
Order By: Relevance
“…Innervation of the periphery nerve has been observed in human tendon and emerging evidence suggests that periphery neuropeptides play a role in tendon healing 13,17,18 . Prior studies have indicated that the expression of sensory neuropeptides (CGRP and SP) in the skeleton was mechanosensitive 15,39 . This study demonstrates the involvement of mechanosensitive neuropeptides in healing enthesis, according to qRT‐PCR and immunochemistry results showing that the expression of CGRP and SP at the healing site increased when mice subjected to treadmill running.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…Innervation of the periphery nerve has been observed in human tendon and emerging evidence suggests that periphery neuropeptides play a role in tendon healing 13,17,18 . Prior studies have indicated that the expression of sensory neuropeptides (CGRP and SP) in the skeleton was mechanosensitive 15,39 . This study demonstrates the involvement of mechanosensitive neuropeptides in healing enthesis, according to qRT‐PCR and immunochemistry results showing that the expression of CGRP and SP at the healing site increased when mice subjected to treadmill running.…”
Section: Discussionmentioning
confidence: 51%
“…Among the periphery neuropeptides, calcitonin gene‐related peptide (CGRP), substance P (SP) and peripheral neuropeptide Y (NPY) are the most commonly investigated. The regulatory roles of these neuropeptides in bone and joint physiology have been documented 14,15 . Expression of CGRP, SP, and NPY were reported to increase in both animal models of tendon injury and clinical specimen, suggesting a potential role for periphery nerve system participating in the progress of tendinopathy and tendon healing 16‐18 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Continuous hyperglycaemia causes peripheral nerve injury. Once injured, the peripheral nerves lose their normal physiological function to increase blood flow as well as protecting bone resorption and reconstruction (Qiao et al, 2019). Eventually, the injury to the peripheral nerve causes the loss of the self‐protective function of the skin of the foot and joints of patients with hyperglycaemia.…”
Section: Introductionmentioning
confidence: 99%